Emotional dependence and self-esteem as predictors of psychological violence in women entrepreneurs - Mamani-Benito, Oscar (2023)
In order to determine how emotional dependence and self-esteem predict psychological violence in Peruvian women entrepreneurs, a predictive cross-sectional study was conducted, involving 180 women entrepreneurs to whom the Psychological Maltreatment Inventory (PMWI), the Emotional Dependence Questionnaire (EDC) and the Stanley Coopersmith Self-Esteem Inventory (Form “C”) were applied. The results show significant correlations between psychological violence, self-esteem and emotional dependence; also, it was found that education level, marital status, self-esteem level and emotional dependence are predictors of psychological violence. It is concluded that low levels of self-esteem and high levels of emotional dependence can predict high levels of psychological violence in Peruvian women entrepreneurs.